Designation of newly identified mutagen-sensitive mutations in Neurospora crassa and their linkage data - H. INOUE; C. ISHII (Fungal Genetics Reports, 1990)
Two years ago, Dr. Käfer and Dr. Schroeder independently summarized genetic information on mutagen-sensitive mutants in Neurospora crassa (Fungal Genetics Newsletter 35:11-13, 1988; DNA Repair 3:77-98, 1988). So far, 30 genetic loci related to mutagen-sensitivity have been indentified. The mutants are more sensitive to UV, X-rays and/or chemical mutagens than the wild-type strain. We have studied DNA-repair mechanisms of Neurospora for several years. During the study, several mutagen-sensitive mutants were isolated and the mutations were mapped. To confirm that they are mutations in new genes, we tested allelism between these mutations and previously reported mutagen-sensitive mutations. Here, new mutations are listed and new mus numbers are given to them as follows.